An Empirical Analysis of the Contagion Risk in the Stock Markets: Evidence with E-GARCH VaR Model - Gao, Song (2014)
This paper examines contagion risk among both current Eurozone Crisis and Asian Crisis in 1997 with daily stock prices during the crisis periods. Three types of financial markets are included to check the risk spillover, which are developed countries (G7 group), emerging countries (BRICs countries) and benchmark countries (Spain, Portugal, Greece and Ireland for Eurozone Crisis, while Indonesia, South Korea and Thailand for Asian Crisis). E-GARCH (1, 1) VaR model with Generalized Error Distribution (GED) is applied for each stock index for evaluating the volatility. Also, Granger Causality test is used to check whether there exists risk spillover. It is found that there is statistically significant evidence of contagion effect contagion risk among both current Eurozone Crisis and Asian Crisis.